MENGGALI POTENSI INTELEKTUAL MAHASISWA DENGAN STRATEGI PEMBELAJARAN AQUA: A QUESTION AND ANSWER - Dardiri*, Dardiri (Belajar Bahasa, 2016)
The background of this research is that there was a tendency of passive behavior of the students during the process of teaching and learning. The students were only taking a little chances to be activity participate in the classroom. This leads to the tendency of having one-way communitation during teaching and learning process. Student were only receive information, taking notes and agreeing to the teacherâs explanation write out any interactive comunication. Learning strategy which is called AQUA is used as the alternative to solve the problem. The objectives of this research are (a) to describe the process of learning by using AQUA to explore the intelectual potential of the students, and (b) to describe the intelectual potential which was explored by using AQUA strategy. The subjects of the study are the students of Bahasa Indonesia in the Laguage and Literature Departement of Muhammadiyah University of Jember. The collection data technique is used are portofolio, observation, questionaire, and interview. The result of the research shows that the AQUA strategy is able to explore the intelectual potential of the students. It can be seen from the inprovement of intelectual potential through AQUA both individually and classically.Key words: passive behavior , intellectual potention, question-answer.